ANALISA KONSISTENSI, KOMUNIKASI PERSUASIF DAN FOKUS KREATOR DALAM LIVE TIKTOK TERHADAP VIEWERS AND FOLLOWERS ON LIVE ROOM SINTESA - Nika Sintesa; Ditta Kristina Putri (AKUNTANSI 45, 2022)
This research is entitled "Analysis of consistency, communication, creator focus in Tiktok towards viewers and followers on live room synthesis". The use of social media that is being widely discussed is tick tok, where tiktok is one of the applications that is widely used by the public, especially teenagers and adults who focus on a variety of activities that can be carried out according to their individual needs, whether to become an affiliate. , entertainment or other educational content in the form of account development to increase followers and viewers when doing live streaming. The use of the tiktok application can be used by using a mobile phone, wherever and whenever and by anyone according to their individual needs. Tiktok is a Chinese social network and music video platform launched in September 2016. The demand when playing tiktok, especially during live streaming, is when there is consistency both in the live room and also making one content created. TikTok users are required to be creative in creating content. The application allows users to create their own short music videos. The theory used in this study is cognitive social theory developed by Albert Bandura and Implementation of Creativity Theory developed by Wallas. The research method used in this study is a qualitative method with a descriptive and phenomenological approach, using data collection methods by means of interviews, observation and documentation. Informants in this study consisted of main informants and supporting informants.